The knowledge management of managers. The virtual experience of the Atenea network - Joaquín Gairín Sallán (ADIDE Federación, 2008)
This article provides a description of a new management model which allows us to produce, share and manage knowledge through an intensive use of the internet by different people. Joint experiments developed with school Headmasters proves possible the interaction, discussion and creation of products between people with responsibility in different schools as well as scholars and government department agents who do not need to know one another, but simply share an interest in certain matters.